Implementation and operation of incident learning across a newly‐created health system. (17th September 2018) - Schubert, Leah; Petit, Josh; Vinogradskiy, Yevgeniy; Peters, Rick; Towery, Jack; Stump, Bryan; Westerly, David; Ridings, Jane; Kneeland, Patrick; Liu, Arthur
Abstract: Purpose: The purpose of this work is to describe our experience launching an expanded incident learning system for patient safety and quality that takes into account aspects beyond therapeutic dose delivery, specifically imaging/simulation incidents, medical care incidents, and operational issues. Methods: Our ILS was designed for a newly created health system comprised of a midsized academic hospital and two smaller community hospitals. The main design goal was to create a highly sensitive system to capture as much information throughout the department as possible. Reports were classified according to incidents and near misses involving therapeutic radiation, imaging/simulation, and patient care (not involving radiation), unsafe conditions, operational issues, and accolades/suggestions. Reports were analyzed according to impact on various steps in the process of care. Actions made in response to reports were assessed and characterized by intervention reliability. Results: A total of 1125 reports were submitted in the first 23 months. For all three departments, therapeutic radiation incidents and near misses consisted of less than one‐third of all reports submitted. For the midsized academic department, operational issues and unsafe conditions comprised the largest percentage of reports (70%). Although the majority of reports impacted steps related to the technical aspects of treatment (simulation, planning, and treatment delivery), 20% impacted other steps such as scheduling or clinic visits. More than 160 actions were performed in response to reports. Of these actions, 63 were quality improvement interventions to improve practices, while 97 were learning actions for raising awareness. Conclusions: We have developed an ILS that identifies issues related to the entire process of care delivery in radiation oncology, as evidenced by frequent and varied reported events. By identifying a broad spectrum of issues in a department, opportunities for improvement can be identified.